2018
DOI: 10.2147/amep.s143151
|View full text |Cite
|
Sign up to set email alerts
|

Perception of academic stress among Health Science Preparatory Program students in two Saudi universities

Abstract: The Health Science Preparatory Program (HSPP) is a special program that aims to enhance the educational preparedness of students for participation in a health sciences career. Students spend their first university year in a combined extensive teaching program before they can be assigned to a particular health science specialty. It is thought that students enrolled in a highly competitive environment such as HSPP with a long list of potential stressors, including developmental, academic overload, language barri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
2
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 10 publications
3
32
2
5
Order By: Relevance
“…Finally, gender, monthly income (pocket money), and satisfaction with the field of study are not significantly associated with perceived stress in this study whereas the significant association was found on a similar study conducted at Debrebran University and study in two Saudi universities, respectively [21,31].…”
Section: Discussioncontrasting
confidence: 80%
“…Finally, gender, monthly income (pocket money), and satisfaction with the field of study are not significantly associated with perceived stress in this study whereas the significant association was found on a similar study conducted at Debrebran University and study in two Saudi universities, respectively [21,31].…”
Section: Discussioncontrasting
confidence: 80%
“…Previous studies in humans provided similar evidence that stress induces an increase of pro-inflammatory Th1 cytokines [119,120,121]. For instance, academic stress, referred to as the body’s response to academic-related workload that goes beyond the adaptive capabilities of students [122], was shown to significantly increase the production of interferon-gamma (IFNγ) and tumor necrosis factor alpha (TNFα) [119]. Acute stress can also upregulate anti-inflammatory cytokines including IL10, while independently inhibiting pro-inflammatory cytokines such as TNFα [123].…”
Section: Stress and Intestinal Microbiota: Bidirectional Relationsmentioning
confidence: 90%
“…These academic -related events that can cause distress to adolescents are referred to as academic stress. Academic stress can be defined as the students' body response to any academic -related demands that surpass their coping abilities (Wilks as cited in Alsulami et al, 2018). Mazo (2015) pointed out that the common stressors of students are related to their academic subjects -various requirements, projects, quizzes, examinations and recitations, their finances, family problems, romantic relationships, and even with their school professors.…”
Section: Introductionmentioning
confidence: 99%